Catalytic oxidation of Hg0 in flue gas over Ce modified TiO2 supported Co-Mn catalysts: Characterization, the effect of gas composition and co-benefit of NO conversion. (15th August 2017) - Li, Honghu; Wang, Shengkai; Wang, Xu; Tang, Nian; Pan, Siwei; Hu, Jiangjun
Highlights: Cox Mn5 /TiCey catalysts exhibited good capacity of catalytic oxidation of Hg 0 and NO. Ce species existed mainly in amorphous phase. Co promoted the generation of Mn2 O3 but obstructed the dispersion of MnOx. Multiple redox couples and surface oxygen species contributed to Hg 0 and NO oxidation. O2 promoted the oxidation activity but SO2 generally suppressed it. Abstract: A series of Ce modified TiO2 supported Co-Mn catalysts (Cox Mn5 /TiCey ) prepared by sol-gel method and impregnation method were evaluated for simultaneous catalytic oxidation of Hg 0 and NO in the simulated flue gas. Results showed that the catalysts exhibited good capacity of simultaneous catalytic oxidation of Hg 0 (around 70%) and NO (around 40%) at 300 °C using a simulated flue gas (Hg 0, NO, SO2, O2, H2 O and balanced N2 ). These catalysts were investigated in detail by means of N2 adsorption-desorption, XRD, Raman spectroscopy, TEM and XPS. The characterization results indicated that physical characteristics of catalysts were not the main contributor for Hg 0 and NO oxidation. Ce species existed mainly in amorphous phase. The addition of CeOx might lead to a migration of Co and Mn species from bulk to surface. The addition of Co could promote the generation of Mn2 O3 but obstruct the dispersion of MnOx on the surface of catalyst. An appropriate increasing loading amount of CoOx or CeOx would be preferable for the improvement of activity performance. The presence of Co 3+ /Co 2+, Mn 4+ /Mn 3+ and Ce 4+ /Ce 3+ redox couples as well as surface oxygen species contributed to the Hg 0 and NO oxidation. A possible synergetic effect Among Co, Mn and Ce species might improve the activity further. Furthermore, an increased oxygen concentration could facilitate the Hg 0 and NO oxidation. NO was observed to promote Hg 0 oxidation with the presence of O2 . SO2 led to a certain decrease of Hg 0 oxidation efficiency due to the competitive adsorption·H2 O had a slightly inhibitory impact on Hg 0 oxidation. Moreover, NO oxidation was more susceptible to SO2 than Hg 0 oxidation over the catalyst.